2009
DOI: 10.1016/j.topol.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

On affine groups admitting invariant two-point sets

Abstract: A two-point set is a subset of the plane which meets every line in exactly two points. We discuss previous work on the topological symmetries of a two-point set, and show that there exist subgroups of S 1 which do not leave any two-point set invariant. Further, we show that two-point sets may be chosen to be topological groups, in which case they are also homogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…We will choose X α in two steps. First, we will extend P to Q so as to satisfy conditions (1) -(4), and then we will extend Q to X α so as to preserve these properties and to additionally satisfy condition (5).…”
Section: The Existence Of Delicate κ-Point Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will choose X α in two steps. First, we will extend P to Q so as to satisfy conditions (1) -(4), and then we will extend Q to X α so as to preserve these properties and to additionally satisfy condition (5).…”
Section: The Existence Of Delicate κ-Point Setsmentioning
confidence: 99%
“…The second motivation for our work is a desire to better understand the structure of two-point sets and to follow a line of research started by Chad and Suabedissen [4,5]. These papers have studied autohomeomorphims of two-point sets, and their main results include the facts that two-point sets may be chosen to be rigid or homogeneous or to have isometry group isomorphic to any subgroup of S 1 of cardinality less than c. These results examine a two-point set by looking for similarity within itself; our results will examine a two-point set by looking for similarity with other distinct types of geometric objects.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], it was shown that any subgroup of S 1 of cardinality less than c is the isometry group of some two-point set and that there exist proper subgroups of S 1 of cardinality c which are the isometry group of some two-point set. In [2], it was shown that there exist proper subgroups of S 1 which are not the isometry group of any two-point set. Given G ≤ S 1 with coset representatives enumerated by g α : α < κ , a two-point set X with isometry group G is of the form α<κ (r α g α G∪s α g α G) for some real-valued sequences r α : α < κ and s α : α < κ .…”
mentioning
confidence: 99%